Comparative Study Of Oral Changes In Pregnant Women Compared To Non Pregnant Women Coming To Nims Hospital And Nims Dental College In Rural Area Of Jaipur District - Bhardwaj, Sukanya; Sunil, M. K.; Sharma, Rohit; Singh, Beer; Bhoomi, Bhoomi; Singh, Akanksha (Journal of Neonatal Surgery, 2025)
Aim: Pregnancy brings about significant physiological and hormonal changes that influence various body systems, including the oral cavity. These changes can lead to distinct oral health conditions that are more commonly observed during pregnancy. The objective of this study is to assess the prevalence of oral health issues specifically associated with pregnancy and to compare their incidence between pregnant women and control group. Materials and Methods: The study involved 110 pregnant women and 110 women in the control group, all between the ages of 18 and 35. Participants were initially identified at the Gynecology Department of NIMS Medical Hospital and later referred to the Oral Medicine and Radiology Department of NIMS Dental College for further assessment. Key oral health indicators, such as the Gingival Index (GI), Decayed, Missing, and Filled Teeth (DMFT) score, and Plaque Index (PI), were measured. Results: Pregnant women demonstrated a significantly higher occurrence of aphthous ulcers and dental erosion. Furthermore, their GI, PI, and DMFT scores were markedly elevated in comparison to the control group, reflecting poorer overall oral health. Conclusion: Poor oral hygiene, increased gingival inflammation, and a higher prevalence of periodontal disease were observed in pregnant women compared to the control group. It is essential to educate women about the critical role of oral health during pregnancy and the potential effects these conditions can have on both maternal and fetal well-being